Optimising Zakat for Empowering Micro Enterprises in Pangkajene Kepulauan Regency, Indonesia: A Pathway to Economic Development - Anwar, Muhammad; Mahsyar, M.; Semaun, Syahrian (Golden Ratio of Data in Summary, 2025)
This study examines the role of zakat in empowering micro-enterprises in Pangkep Regency, focusing on effective management strategies to optimize its impact on economic development. The study aims to address two key questions: (1) How does Baznas Pangkep Regency, Indonesia, implement zakat management to support micro-enterprise empowerment? (2) How effective are the empowerment programs in enhancing the capacity and independence of the mustahik? This research employs a phenomenological approach using qualitative methods. The analytical framework is based on Henry Fayol's management theory and Marc A. Zimmerman's empowerment theory. Data was collected through in-depth interviews with Baznas administrators and beneficiaries (mustahik), direct observation of program implementation, and document analysis of policies and activity reports from Baznas. The findings reveal that Baznas Pangkep Regency applies five management functions in zakat management: planning, organizing, directing, coordinating, and supervising. Planning is conducted through socialization and zakat fund mobilization strategies. Organizing involves implementing micro-enterprise empowerment programs through skills training and business capital distribution. Directing is done by assigning personnel according to their expertise to ensure program effectiveness. Coordination occurs through a transparent and participatory administrative system, while supervision includes internal and external audits to ensure compliance with Sharia principles and zakat fund accountability. The impact of the empowerment programs shows an increase in the income and business scale of the mustahik, contributing to their overall well-being. However, key challenges identified include the lack of continuous training and limited business mentoring. Based on Zimmerman's empowerment theory, the program has enhanced the mustahik's capacity to manage their businesses more independently. This study recommends that Baznas enhance program effectiveness by strengthening continuous training, business mentoring, and developing innovative zakat fund mobilization and distribution strategies to support the sustainability of micro-enterprise empowerment programs.